2020
DOI: 10.31219/osf.io/ek6aq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Gaps in the Chilean Young Investigator Grant and the Potential Impact of COVID-19 Lockdowns in 2020

Abstract: Gender gaps are a problem in science, impeding the advancement of women. While some progress has been made in recent years, the COVID-19 lockdowns in 2020 could aggravate the gender gap even more, with female researchers taking on more responsibilities of care work and domestic labor than men while working from home. The present study analyzed the number of proposals submitted by women to the Chilean Young Investigator Grant (Fondecyt de Iniciación en Investigación) competition 2020, whose application period c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Studies on gender differences among academics during COVID-19 have found that women academics perceive more negative outcomes than their male colleagues. Early studies found gendered discrepancies in the proportions of journal submissions (Andersen et al 2020;Squazzoni et al 2020), preregistration andpreprint (Vincent-Lamarre et al 2020), and in grant applications (Garrido-Vásquez et al 2020) across several disciplines (Oleschuk 2020). Women academics reported decreases in first author submissions, and co-authored article submissions from two months prior to stay-at-home orders to two months into these orders (Krukowski et al 2021).…”
Section: The Gendered Effects Of the Covid-19 Pandemic Among Knowledg...mentioning
confidence: 99%
“…Studies on gender differences among academics during COVID-19 have found that women academics perceive more negative outcomes than their male colleagues. Early studies found gendered discrepancies in the proportions of journal submissions (Andersen et al 2020;Squazzoni et al 2020), preregistration andpreprint (Vincent-Lamarre et al 2020), and in grant applications (Garrido-Vásquez et al 2020) across several disciplines (Oleschuk 2020). Women academics reported decreases in first author submissions, and co-authored article submissions from two months prior to stay-at-home orders to two months into these orders (Krukowski et al 2021).…”
Section: The Gendered Effects Of the Covid-19 Pandemic Among Knowledg...mentioning
confidence: 99%
“…It is important to point out that increased gender disparity in research productivity as a result of pandemic rules and switching to online teaching is not a phenomenon restricted to Europe and North America. There are a plethora of studies showing similar results globally, including Brazil [41], Mexico [42], South Africa [43], Pakistan [44], Turkey [45], Chile [46], West African countries [47], and Australia [48] to give only a handful of examples.…”
Section: Post-pandemic Gender Inequality In the Academiamentioning
confidence: 99%